Workplace Stress And Pregnancy Complications: A Cross-Sectional Study Among Working Pregnant Women - Lara Santi; Hanny Yuli Andini; Rochmawati (Sekolah Tinggi Ilmu Kesehatan Bina Bangsa (BBM) Majene, 2026)
Background: Workplace stress during pregnancy contributes to adverse maternal-fetal outcomes, including preterm birth, low birth weight, and pregnancy-induced hypertension. Limited research has examined this relationship in the Indonesian population. Objective: This study examined associations between workplace stress levels and pregnancy complications among working pregnant women. Methods: Cross-sectional study involving 160 pregnant women in urban Indonesia using the Work Stress Assessment Scale (WSAS), Pregnancy Experience Scale (PES), and comprehensive demographic questionnaires. Multivariable logistic regression analyzed relationships between workplace stress and pregnancy complications, adjusting for demographic and environmental factors. Results: Participants had an average work stress score of 79.52±11.87, pregnancy experience score of 81.88±11.84, and lifestyle and work environment factors of 80.04±11.60. There was a strong positive correlation between all work stress variables (r=0.8180.961, p<0.001). Work stress was significantly associated with pregnancy complications in the initial model (OR=0.077; 95% CI: 0.031-0.190; p<0.001); however, the OR below 1.0 likely reflects healthy worker survivor bias rather than a true protective effect. Work stress lost statistical significance in the final model (OR=0.500; p=0.325) after inclusion of lifestyle and work environment factors, which emerged as the sole independent predictor (OR=0.080; 95% CI: 0.0180.349; p=0.001). Conclusions: While initial models showed significant associations between work stress and pregnancy complications, the final model indicated that concrete work environment factors—such as working hours, rest periods, and physical hazards—were the dominant predictors, mediating the perceived stress-complication relationship. The counterintuitive OR direction and the loss of significance for work stress in the fully adjusted model highlight important methodological limitations of the cross-sectional design. Healthcare providers should incorporate occupational exposure assessment into routine antenatal care, with emphasis on modifiable working conditions.